Synergizing Oil Palm Landscapes, Agroforestry, Eco-Tourism, and Rural Economy: A Review on Pathways to Sustainable Development - Loso Judijanto (Malikussaleh University, Aceh, Indonesia, 2025)
The rapid expansion of oil palm monocultures in tropical regions has been unfairly accused of being the sole cause of environmental degradation, socio-economic imbalances, and diminished biodiversity. As sustainability and ecotourism gain global momentum, agroforestry within oil palm landscapes emerges as a promising solution to reconcile ecological conservation with rural economic development. This study investigates the potential of agroforestry-based systems in oil palm plantations as sustainable eco-tourism destinations. The objective of this research is to explore how agroforestry practices can restore ecological function, diversify local economies, and enhance community participation through eco-tourism integration. This qualitative study adopts a Systematic Literature Review (SLR) methodology guided by the PRISMA protocol. The data were collected from the ScienceDirect database using refined Boolean keyword combinations. A total of 1,005 articles were initially identified, narrowed down to 31 relevant peer-reviewed research articles published between 2020 and 2025 after applying specific inclusion and exclusion criteria related to topic, time frame, document type, and open access availability. Thematic analysis was applied to synthesize findings from the selected articles. Results indicate that agroforestry significantly enhances biodiversity, improves microclimates, sequesters carbon, diversifies income sources, and strengthens community governance within tourism ventures. Ecological, economic, and social synergies suggest that agroforestry in oil palm systems is a viable model for regenerative tourism. In conclusion, agroforestry has strong potential to transform oil palm landscapes into inclusive, resilient, and ecologically sound eco-tourism destinations. Future studies should expand interdisciplinary evaluation frameworks and assess long-term impacts through longitudinal data.